Redescription of the hagfishes (Myxinidae: Eptatretus) from southern Africa. Issue 7 (9th August 2017) - Mincarone, Michael Maia
ABSTRACT: The hagfishes of the genus Eptatretus (Myxinidae) from southern Africa are known from three poorly studied species: Eptatretus hexatrema, a common species from Namibia and South Africa; Eptatretus profundus, known only from the holotype collected off Cape Point (South Africa); and Eptatretus octatrema, known from two syntypes from the Agulhas Bank (South Africa). Taxonomic, morphological and distributional information about these three species are reviewed and updated based on the examination of additional specimens collected in South African waters. Eptatretus hexatrema differs from all congeners by having six pairs (rarely seven) of gill apertures arranged in a straight line, 3/2 multicusp pattern of teeth, total cusps 44–49, trunk pores 53–60, total pores 93–107, preventral length 45.1–57.4% TL, tail length 11.6–14.3% TL, tail depth 5.7–8.1% TL, and two bilaterally symmetrical nasal-sinus papillae. Eptatretus octatrema differs from all congeners by having usually eight (some specimens with seven) pairs of gill apertures arranged in a straight line, 3/2 multicusp pattern of teeth, 42–46 total cusps, 22–26 prebranchial pores, 63–68 trunk pores, 104–117 total pores, and two bilaterally symmetrical nasal-sinus papillae. Eptatretus profundus differs from all congeners by having five pairs of gill apertures arranged in a straight line, 3/2 multicusp pattern of teeth, total cusps 42–46, prebranchial pores 12–15, branchial pores 4–5, trunk pores 48–52, tail pores 15–17, total pores 81–86, and body depth at PCD 7.0–9.7% TL. An identification key for the hagfishes from southern Africa is provided and the conservation status of E. octatrema, a species considered to be Critically Endangered, is discussed in light of the new findings.